The Effect of Learners’ Attitude, Motivation, and Beliefs toward Willingness to Communicate in EFL Classroom (Conference on English Language Teaching, 2023)
Willingness to communicate in English foreign language has become an essential context that is investigated in the field of language research, especially in communication competence studies. Hence, the present study aimed to investigate the influence of students’ attitude, motivation, and beliefs toward WTC. The purpose of this study was to determine whether there were or not any significant influences of students’ attitude, motivation and beliefs toward willingness to communicate in EFL classroom at SMA Negeri 1 Pagerbarang. The study used inferential quantitative with survey research design. This research was conducted at 11th and 12th grade students of SMA Negeri 1 Pagerabarang with the total 85 students of SMA Negeri 1 Pagerbarang participated as respondents. The instrument consisted of 40 items. The analysis data of this research used multiple linear regression analysis. the data were calculated SPSS version 26.0. Based on the results, it was concluded that partially, there was a positive and significant influence of learners’ attitude toward willingness to communicate. However, there was no significant influence of motivation and learners’ beliefs toward willingness to communicate in EFL classroom. In reference to communicative competence, the teacher should consider the factors influenced students’ willingness to communicate in EFL classroom to create meaningful interaction and students’ active engagement.